PENGARUH PENGGUNAAN TEPUNG LIMBAH PERTANIAN UMBI WORTEL (Daucus carrota. L) DALAM RANSUM TERHADAP KECERNAAN PROTEIN PADA AYAM BROILER - Pramudyah Sejati; Luthfi Djauhari Mahfudz; Vitus Dwi Yunianto (Universitas Wahid Hasyim, 2017)
This research aims to assess the effect of using agricultural waste carrot root of the digestibility of protein in the ration of broiler chickens. The material used is broiler strain Lohmann age of 7 days with a body weight of 181.40 ± 11.31 grams of 144 birds. Material feed used consisting of yellow corn, rice bran, Meat Bone Meal, Poultry Meat Meal, soybean meal, mineral mix and flour carrots. Carrot flour used in the diet for 4 weeks. The tools used for data retrieval protein digestibility is a tray container excreta, hand sprayer, scales and laboratory equipment analysis of dietary protein and excreta. The research used a completely randomized design with 4 treatments and 6 replications, each unit consisting of six broiler chickens. Treatment applied is T0 (without flour carrots), T1 (diet with 2% flour carrots), T2 (diet with 4% flour carrots) and T3 (diet with 6% flour carrots). The measured parameters which include feed consumption, the consumption of protein, and protein digestibility. The data were processed using analysis of variance. The results showed that the use of agricultural waste flour carrot root no significant effect (P> 0.05) on feed consumption, the consumption of protein, and the protein digestibility of broiler chickens. The use of carrot flour is still low due to beta-carotene as provitamin A activity 1/6 of vitamin A. Keywords: broiler chicken, carrot flour, consumption of protein, digestible protein.